Composition and structure of the forest-páramo transition in the Guantiva-La Rusia corridor (Colombia) - Olaya Angarita, Jeison Adrian; Díaz-Pérez, Carlos Nelson; Morales-Puentes, María Eugenia (Revista de Biología Tropical, 2019)
The altitudinal forest – paramo transition area, in its lower limit is characterized by the transition through the high Andean forest to high and low forest bushes, and is upper limit to the turnover between the low shrubs to herbaceous. Samplings were carried out in three localities of the Guantiva - La Rusia complex in the Western flank, through a 100 m2 parcels for the forest coverage and 50 m2 for the shrub and the herbaceous coverages, with an altitudinal difference of 100 m between altitudinal areas. We recorded 70 families, distributed in 157 genera and 302 species. The Asteraceae family were the most diverse with 16 genera and 39 species; likewise, Miconia was the most diverse with 14 species. Diversity indexes revealed that the most dominant in species composition were the herbaceous areas; regarding to diversity, the Onzaga-Susacon forest is 1.9 and 1.3 times more diverse than Belen and Duitama respectively. This research allowed identifying the transitional area through the transformation of the vascular flora physiognomy and diversity in the altitudinal gradient Western flank complex, that transition area is in Duitama between 3 394 - 3 516 m, in Belen 3 411 - 3 649 m and in Onzaga-Susacon 3 300 - 3 390 m.